A new agent developed by biotransformation of polyphyllin VII inhibits chemoresistance in breast cancer - He, Dong-Xu (Oncotarget, 2015)
Biotransformation by the endophytes of certain plants changes various compounds, and this ‘green’ chemistry becomes increasingly important for finding new products with pharmacological activity. In this study, polyphyllin VII (PPL7) was biotransformed by endophytes from the medicinal plant Paris polyphylla Smith, var. yunnanensis. This produced a new compound, ZH-2, with pharmacological activity in vitro and in vivo. ZH-2 was more potent than PPL7 in selectively killing more chemoresistant than chemosensitive breast cancer cells. ZH-2 also re-sensitized chemoresistant breast cancer cells, as evidenced by the improved anti-cancer activity of commonly-used chemotherapeutic agent in vitro, in vivo, and in clinical samples. This anti-chemoresistance effect of ZH-2 was associated with inhibiting the epithelial-mesenchymal transition (EMT) pathway. Taken together, our findings are the first one to link biotransformation with a biomedicine. The results provide insights into developing new pharmacologically-active agents via biotransformation by endophytes.